Ascorbic acid protects Coccomyxa subellipsoidea against metal toxicity through modulation of ROS/NO balance and metal uptake - Kováčik, Jozef; Rotková, Gabriela; Bujdoš, Marek; Babula, Petr; Peterková, Viera; Matúš, Peter (Journal of hazardous materials, 2017)
Impact of exogenous ascorbic acid (AsA, 100μM) on acute metal toxicity (Pb and Hg, 24h of exposure to 100μM) in unicellular green alga Coccomyxa subellipsoidea was studied. Hg (often extensively) depleted amount of pigments, potassium, soluble proteins, endogenous AsA, non-protein thiols and nitric oxide signal but elevated ROS signal and activities of catalase and superoxide dismutase. Responses to Pb application (if any) were less visible with ROS signal being slightly elevated and amount of non-protein thiols being slightly reduced. Exogenous AsA considerably improved mainly Hg-induced damage at the level of oxidative stress and physiological parameters and evoked an increase in nitric oxide signal. Maximum amount of total Hg was almost 4-fold higher than that of Pb (36.5 vs. 9.73mg/g DW) and AsA depleted both total and intracellular accumulation. At the level of ascorbate-related proteins, exogenous AsA suppressed metal-induced expression and activity of MDHAR and APX but not of DHAR, which may indicate a role of DHAR in algal stress tolerance. Our data suggest that given Coccomyxa species is suitable candidate for remediation of Hg or Pb and that ascorbic acid effectively ameliorates metal-induced toxicity without side effects.
Keywords: olovo; Ascorbate Peroxidases; oxidační stres; antioxidancia; Lead; Heavy metals; Oxidative stress; Oxidoreductases; kyselina askorbová; Chlorophyta; rtuť; Chlorophyll; Mercury; Ascorbic Acid; oxidoreduktasy; chlorofyl; Antioxidants; Fluorescence microscopy; askorbátperoxidasa; RT-PCR; Superoxide Dismutase; Oxidative Stress; superoxiddismutasa